Reproductive Biology of the Critically Endangered Valcheta frog, Pleurodema somuncurense (Anura: Leptodactylidae), from Patagonia, Argentina - Velasco, Melina Alicia (2017)
Amphibians exhibit a great diversity of reproductive modes. Nevertheless, reproductive biology is still unknown for several threatened Neotropical species, including the Critically Endangered microendemic Valcheta frog, Pleurodema somuncurense. This paper looks at the reproductive biology of this species, describes its behavior, amplexus, spawning, clutches, embryonic development and breeding microhabitats, and discusses differences and similarities between it and the other Patagonian species included in the P. thaul clade: P. bufoninum and P. thaul. Fieldwork was conducted from 2013–2015 in the headwaters of Valcheta Stream (northern Patagonia, Argentina), over the whole known range of P. somuncurense. We also added information from an ex situ survival colony of this species. Pleurodema somuncurense has prolonged seasonal reproductive activity during spring–summer and presents features of both explosive and prolonged breeders. The Patagonian species of the P. thaul clade all have inguinal amplexus and lay pigmented eggs in gelatinous strings. During inguinal amplexus, the male P. somuncurense arches its body, bringing its vent closer to the female’s, while contracting its body muscles rhythmically and moving its pelvic girdle up and down while the female spawns the eggs. We occasionally recorded mating calls, release calls, and warning vibrations. Although there are similarities among the three species, P. somuncurense has some specific features, such as scramble competition, which has not yet been recorded for any other species in the genus, and the mating call, although better records in natural conditions are needed for detailed analysis and more robust comparison. Because the breeding microhabitats used by P. somuncurense are currently under disturbance from livestock, their protection should be a matter of concern.